(untitled) (UKLO Proceedings, 2025)
Achieving sustainable development goals (SDGs) is among top national priorities for Western Balkan countries even if the efforts and awareness remain low especially in Albania. Sustainable development education has been integrated to different levels of the curricula of pre-university education and it is part of the curricula of higher education institutions (HEIs) in Albania. Sustainable development education is considered catalyst in raising awareness on SDGs especially among young people. In business related university degrees sustainable development education has been traditionally linked to corporate social responsibility (CSR), business ethics courses or circular economy (CE) courses. The number of dedicated courses and degrees focused in sustainable development has increased over the years. The teaching and learning approach remain traditional. Sustainable development is interdisciplinary. Courses related to sustainable development lack of interdisciplinary approach. The aim of this paper is to explore the integration of interdisplinarity in sustainable development in Albanian HEIs. The approach of this study is qualitative, case study method is used. The study focuses in business ethics course offered by the Department of Management at the Faculty of Business, Aleksandër University of Durrës. The findings suggest that interdisciplinary in this course is needed in order to build transversal competence in terms of sustainable consumption, sustainable production, gender discrimination, sustainable spaces and digital and AI competence.